Analisis Semiotik Charless Sanders Peirce dalam iklan minuman pada Media Elektronik sebagai Alternatif Pemilihan Bahan Ajar di SMA - Fitriani, Fitriani (Universitas Mathla'ul Anwar Banten, 2025)
Charless Sanders Peirce Semiotic Analysis in Drink Advertisements on Electronic Media as an Alternative for Selecting Indonesian Language Teaching Materials in High School. Indonesian and Regional Literature Language Education Study Program, Undergraduate Program (S1) Faculty of Teacher Training and Education, Mathla'ul Anwar University, Banten. This research aims to analyze drink advertisements broadcast in electronic media using Charles Sanders Peirce's semiotic approach. The data sources or research objects were 25 electronic media drink advertisements. In an educational context, this research offers alternative Indonesian language teaching materials at the high school level. The analysis method is carried out by identifying signs such as icons, indices and symbols as well as the meaning contained in the advertisement. Data is collected from various popular and relevant drink advertisements. The results of the analysis show that semiotic elements in advertising not only influence consumer perceptions but can also be used to improve students' understanding of language and socio-cultural context. These findings recommend the use of advertising as an interactive and contextual learning resource in Indonesian language teaching, so that students can be more critical in analyzing the media they consume. It is hoped that this research can contribute to the development of more interesting and relevant language learning methods.